A boy with amblyopia and familial exudative vitreoretinopathy harboring a new mutation of LRP5 and OPA1: A case report - Chen, Chunli; Guo, Sitong; Zhao, Rui; Liu, Shoubin; Wu, Jingjing; Xiao, Yuanyuan; Hou, Simeng; Jiang, Libin (Frontiers in Genetics, 2022)
Background: To report a boy with familial exudative vitreoretinopathy and amblyopia harboring a new mutation of the LRP5 and OPA1 gene abnormality. Case presentation: A 9-year-old boy presented with a two-year history of deteriorating visual acuity in the right eye. His best-corrected visual acuity (BCVA) was -7.00/-1.75 × 100 = 0.3 in the right eye and -2.50/-1.50 × 170 = 0.8 in the left. Two autosomal dominant gene mutation sites were identified in the patient: LRP5 (c.2551C>T, p.His851Tyr) from his father, and OPA1 (c.565G>A, p.Glu189Lys) from his mother. Interestingly, his fraternal twin brother harbored no abnormal gene mutations and his eye tests were normal. Conclusions: This case expands the spectrum of LRP5 gene mutations among Chinese patients with FEVR, and it is the first time to report the patient, harboring both LRP5 and OPA1 gene mutations, have anisometropic amblyopia and strabismus as the primary manifestations. These four family members exhibited individual heterogeneity of phenotypes and genotypes associated with hereditary ophthalmopathy. A comprehensive analysis of clinical phenotypes and genotypes provide clinical clues for improving the level of clinical and genetic diagnosis and a deeper understanding of the disease.